#LibraryLife: A quantitative analysis of social media usage, content, and engagement at the Vancouver Public Library - Vander Kooy, Sam (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2021)
<span data-sheets-value=""1":2,"2":"This paper explores the contents of the Vancouver Public Library’s Facebook, Instagram, Twitter, and YouTube feeds between September 1st and November 30th, 2020 to better understand how each social media platform is being used to communicate with stakeholders. This quantitative content analysis of each platform’s usage, content, and engagement highlights some important trends libraries should be aware of concerning both the use of multiple social media platforms and the evaluation of their current social media strategies."" data-sheets-userformat=""2":8961,"3":"1":0,"11":0,"12":0,"16":12">This paper explores the contents of the Vancouver Public Library’s Facebook, Instagram, Twitter, and YouTube feeds between September 1st and November 30th, 2020 to better understand how each social media platform is being used to communicate with stakeholders. This quantitative content analysis of each platform’s usage, content, and engagement highlights some important trends libraries should be aware of concerning both the use of multiple social media platforms and the evaluation of their current social media strategies.